2020
DOI: 10.1016/j.addma.2020.101162
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of a biocompatible low molecular weight supramolecular hydrogel by dimethylsulfoxide water solvent exchange

Abstract: A fragile and non-thixotropic biocompatible low molecular weight gel is printed in 3D structures by a solvent exchange process. The 3D printing process is based on the continuous extrusion of a solution of a small amphiphile molecule, N-heptyl-D-galactonamide, in dimethylsulfoxide, that forms a gel in contact with water. The diffusion of water in the dimethylsulfoxide / N-heptyl-D-galactonamide solution triggers the self-assembly of the molecule into supramolecular fibers and the setting of the ink. The condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…They often result in large and not well resolved patterns. Given the instant gelation observed with the gelators of our study, better resolved architectures are expected in transposition to 3D printing, as it was observed with N-heptyl-D-galactonamide 44 . In the persepctive of biological applications, the carbohydrate molecular gels developed in this study could be an alternative to peptide hydrogels 11,14 , 19 .…”
Section: -Conclusionsupporting
confidence: 57%
See 1 more Smart Citation
“…They often result in large and not well resolved patterns. Given the instant gelation observed with the gelators of our study, better resolved architectures are expected in transposition to 3D printing, as it was observed with N-heptyl-D-galactonamide 44 . In the persepctive of biological applications, the carbohydrate molecular gels developed in this study could be an alternative to peptide hydrogels 11,14 , 19 .…”
Section: -Conclusionsupporting
confidence: 57%
“…The method has also been transposed to 3D printing, leading to the production of 3D printed fibrillar networks made of only small gellifying synthetic molecules and a high percentage of water 44 . 3D printed structures for cell culture made of only molecular gel, without any polymer are still scarce, because supramolecular hydrogels are very soft hydrogels that hardly sustain the weight of the upper layers.…”
Section: Introductionmentioning
confidence: 99%
“…The DMSO solution with N-heptyl-D-galactonamide (31b) formed injectable gels in a water bath [66]. In a later study, they showed that a DMSO solution of 31b could be injected into a water bath to print a gel on a glass slide covered with a hydrophobic polycarbonate membrane [67]. The gluconamide-based amphiphiles in Figure 23 were generated from cashew nut shell liquid and δ-gluconolactone, which are rather easily available, renewable resources [68].…”
Section: Glyconamide Derivatives By Modification At the Anomeric Posimentioning
confidence: 99%
“…In a later study, Fitremann et.al. showed that solvent exchange can be used to 3D print this non-thixotropic carbohydrate-based supramolecular gel [ 67 ]. Using a syringe pump, XY-translation stage and a handheld Z-adjustable platform, a DMSO solution of N-heptyl-D-galactonamide ( 31b in Figure 22 ) was injected into a water bath to print a gel onto a glass slide covered in a hydrophobic polycarbonate membrane.…”
Section: Applications Of Sugar-based Lmwgsmentioning
confidence: 99%
“…In a previous study, it has been shown that N-heptyl-Dgalactonamide supramolecular hydrogel is suitable for the growth and differentiation of adult human neural stem cell (hNSC) in 3D [20]. Additionally, 3D constructs can be made by 3D printing [32,33]. However, this hydrogel is nearly completely consumed by the cells after 7 days.…”
Section: Introductionmentioning
confidence: 99%